Pharmaceutical Approval Update - Fellner, Chris (P T, 2016)
Elotuzumab (Empliciti) and ixazomib (Ninlaro) for some multiple myeloma patients; Fluad (influenza vaccine, adjuvanted) for immunization of persons 65 years of age and older; and osimertinib (Tagrisso) for certain non–small-cell lung cancers